R. David Arkush y Leo O. Lee (comps.). Land Without Ghosts, Chinese Impressions of America from the Mid-Nineteent Century to the Present. Traducción del chino al inglés de R. David Arkush y Leo O. Lee. Berkeley, CA: University of California Press, 1989. 309 pp. - Connelly, Marisela (Estudios de Asia y África, 1995)
-